2022
DOI: 10.1139/cjc-2021-0117
|View full text |Cite
|
Sign up to set email alerts
|

Itaconate: an antimicrobial metabolite of macrophages

Abstract: Itaconate is a conjugated 1,4-dicarboxylate produced by macrophages. This small molecule has recently received increasing attention due to its role in modulating the immune response of macrophages upon exposure to pathogens. Itaconate has also been proposed to play an antimicrobial function; however, this has not been explored as intensively. Consistent with the latter, itaconate is known to show antibacterial activity in vitro and was reported to inhibit isocitrate lyase, an enzyme required for survival of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…Covalent inhibition is an effective way to limit the function of an enzyme. This mechanism has been leveraged by many organisms to limit the growth of competitors vying for resources (e.g., beta-lactams from the fungal genus Penicillium ) 1 or to fight infections (e.g., itaconate from mammalian macrophages 2 ). The warheads of these covalent inhibitors are sometimes obvious, such as the strained ring of beta-lactams or the α,β-unsaturated carboxylic acid of itaconic acid, while some have subtle mechanisms of covalent inhibition that are not apparent by looking at the functional groups of the inhibitor (e.g., 3-nitropropionate as an inhibitor of isocitrate lyase 3 or wortmannin as a phosphoinositide-3 kinase inhibitor 4 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Covalent inhibition is an effective way to limit the function of an enzyme. This mechanism has been leveraged by many organisms to limit the growth of competitors vying for resources (e.g., beta-lactams from the fungal genus Penicillium ) 1 or to fight infections (e.g., itaconate from mammalian macrophages 2 ). The warheads of these covalent inhibitors are sometimes obvious, such as the strained ring of beta-lactams or the α,β-unsaturated carboxylic acid of itaconic acid, while some have subtle mechanisms of covalent inhibition that are not apparent by looking at the functional groups of the inhibitor (e.g., 3-nitropropionate as an inhibitor of isocitrate lyase 3 or wortmannin as a phosphoinositide-3 kinase inhibitor 4 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of immune-responsive gene 1 (IRG1)/ cis -aconitate decarboxylase (CAD), cis -aconitate is converted to itaconate, which plays an important role in regulating signal transduction and post-translational modification through its immunomodulatory activity. , A previous report has indicated that 4-octyl itaconate (OI), a cell-permeable derivative of itaconic acid, was a crucial anti-inflammatory metabolite by activating the nuclear factor erythroid 2-related factor 2 ( Nrf2 ) to limit inflammatory and modulating type I interferon . Moreover, itaconate exhibited antibacterial effects by inhibiting the activity of isocitrate lyase (ICL) in bacteria . During bacterial infections, itaconate can destroy bacteria and enhance the innate immune response by promoting lysosomal biogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…25 Moreover, itaconate exhibited antibacterial effects by inhibiting the activity of isocitrate lyase (ICL) in bacteria. 26 During bacterial infections, itaconate can destroy bacteria and enhance the innate immune response by promoting lysosomal biogenesis. 27 Therefore, itaconate shows promise for potential applications in the treatment of inflammatory and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%